Terahertz Metasurfaces for Polarization Manipulation and Detection: Principles and Emerging Applications - Yongliang Liu; Yifei Xu; Bo Yu; Wenwei Liu; Zhengren Zhang; Hua Cheng; Shuqi Chen (Advanced Physics Research)
Abstract Terahertz frequencies locating between microwave and infrared regions can record and process optical information for next‐generation information technology such as 6G communication. Metasurfaces, as emerging planar optical components built with micro‐ or nanostructures, enable precise control, and manipulation of electromagnetic waves from near fields to far fields. These subwavelength artificial structures can be engineered to exhibit specific polarization responses, thus holding significant potential for applications in polarization detection. In the terahertz (THz) region, polarization information is crucial for identifying and analyzing the properties of materials in the terahertz. In this review, we focus on recent advances in terahertz metasurfaces for polarization manipulation and detection, including principles and emerging applications. New polarization detection methods such as polarization state conversion, polarization‐selective absorption, polarization‐selective focusing, and vector beam construction are discussed. Finally, it is concluded with a few perspectives on emerging trends and existing challenges in the fields of terahertz polarization manipulation and detection.